2021
DOI: 10.1111/jvh.13565
|View full text |Cite
|
Sign up to set email alerts
|

The effects of hepatitis B virus infection on natural and IVF pregnancy: A meta‐analysis study

Abstract: Background Hepatitis B virus (HBV) has been considered a significant cause of human reproductive failure in different studies; however, there is a considerable disagreement on the true impacts of HBV on female reproduction. This study has evaluated the impact of HBV infection on pregnancy complications in natural pregnancy and also on pregnancy outcomes in women undergoing in vitro fertilization (IVF) treatment. Method We searched Embase, Web of Science, PubMed and Google Scholar databases to identify the pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…Previous studies have found no link between maternal HBV infection and live birth, preterm birth, or pregnancy rates in women undergoing assisted reproductive technology . Our study confirms that maternal HBV serostatus is not associated with pregnancy outcomes in infertile women undergoing FET.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies have found no link between maternal HBV infection and live birth, preterm birth, or pregnancy rates in women undergoing assisted reproductive technology . Our study confirms that maternal HBV serostatus is not associated with pregnancy outcomes in infertile women undergoing FET.…”
Section: Discussionsupporting
confidence: 79%
“…Previous population studies 12,13,[37][38][39][40] on the association of HBV infection with fecundability have shown inconsistent results. Studies 12,37 of women found that HBV-infected persons undergoing assisted reproduction procedures had prolonged durations of infertility.…”
Section: Jama Network Open | Obstetrics and Gynecologymentioning
confidence: 99%
“…Male factors constitute 40 to 50% of all infertility cases [ 5 ]. Pathological agents, especially viruses, play a distinctive role in infertility [ 6 , 7 ]. Viruses as a major cause of fertility problems are able to potentially interfere with reproductive function in men [ 8 ].…”
Section: Introductionmentioning
confidence: 99%